2019
DOI: 10.1002/jsfa.9817
|View full text |Cite
|
Sign up to set email alerts
|

Dietary taurine supplementation decreases fat synthesis by suppressing the liver X receptor α pathway and alleviates lipid accumulation in the liver of chronic heat‐stressed broilers

Abstract: BACKGROUND Chronic heat stress can enhance fat synthesis and result in lipid accumulation in the liver of broilers. To investigate the effects and molecular mechanisms of dietary taurine supplementation on fat synthesis and lipid accumulation in the liver of chronic heat‐stressed broilers, 144 28 day‐old chickens (Arbor Acres) were randomly distributed to normal control (NC, 22 °C, basal diet), heat stress (HS, consistent 32 °C, basal diet), or heat stress plus taurine (HS + T, consistent 32 °C, basal diet +5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 33 publications
(77 reference statements)
2
13
1
Order By: Relevance
“…The organ index is an important parameter reflecting the development status of organs. A recent study [36] reported an increase in the liver index when broilers were reared under chronic HS. There was a weakly significant (p = 0.099) tendency to increase the liver index of HS birds in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…The organ index is an important parameter reflecting the development status of organs. A recent study [36] reported an increase in the liver index when broilers were reared under chronic HS. There was a weakly significant (p = 0.099) tendency to increase the liver index of HS birds in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, it is possible that GABA might activate the adenosine monophosphate-activated protein kinase (AMPK) pathway for regulating fatty acid metabolism [ 11 ]. However, evidence shows that fat synthesis in chickens is under the control of the liver X receptor α (LXRα) pathway [ 47 ]. Therefore, further research is needed to address the mechanism by which GABA could induce a reduction in hepatic fat synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al [ 56 ] reported alteration of serum lipid metabolism in heat-stressed-indigenous slow-growing chickens. Plasma triglyceride and liver enzyme concentrations increased significantly in broilers exposed to chronic heat stress for 14 days [ 57 ]. Spirulina supplementation at 0.5 to 2% reported decreasing serum cholesterol, LDL, total lipids and triglycerides of broilers subjected to heat stress [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%